Results of application of a combination of Doksazozina and Indigala in therapy of men with prostate adenoma I—II stages - V. N. Pavlov; А. А. Kazikhinurov; A. A. Izmaylov; A. V. Boyarko; A. O. Papoyan; R. V. Abdrakhimov (Бюллетень сибирской медицины, 2012)
In work the way of conservative therapy of men with prostate adenoma I—II of a stage with use of a combination of Doksazozina and Indigala different antioxidantiv, antiproliferative and anti-inflammatory properties that has allowed to improve urodynamic indicators is offered and to slow down progressing prostate adenoma, having reduced to a minimum undesirable effects of treatment.